The adjuvants dmLT and mmCT enhance humoral immune responses to a pneumococcal conjugate vaccine after both parenteral or mucosal immunization of neonatal mice - Molina Estupiñan, Jenny Lorena; Aradottir Pind, Audur Anna; Foroutan Pajoohian, Poorya; Jonsdottir, Ingileif; Bjarnarson, Stefania P. (Frontiers in Immunology, 2023)
Immaturity of the neonatal immune system contributes to increased susceptibility to infectious diseases and poor vaccine responses. Therefore, better strategies for early life vaccination are needed. Adjuvants can enhance the magnitude and duration of immune responses. In this study we assessed the effects of the adjuvants dmLT and mmCT and different immunization routes, subcutaneous (s.c.) and intranasal (i.n.), on neonatal immune response to a pneumococcal conjugate vaccine Pn1-CRM197. Pn1-specific antibody (Ab) levels of neonatal mice immunized with Pn1-CRM197 alone were low. The adjuvants enhanced IgG Ab responses up to 8 weeks after immunization, more after s.c. than i.n. immunization. On the contrary, i.n. immunization with either adjuvant enhanced serum and salivary IgA levels more than s.c. immunization. In addition, both dmLT and mmCT enhanced germinal center formation and accordingly, dmLT and mmCT enhanced the induction and persistence of Pn1-specific IgG+ Ab-secreting cells (ASCs) in spleen and bone marrow (BM), irrespective of the immunization route. Furthermore, i.n. immunization enhanced Pn1-specific IgA+ ASCs in BM more than s.c. immunizatiofimmu.2022.1078904n. However, a higher i.n. dose of the Pn1-CRM197 was needed to achieve IgG response comparable to that elicited by s.c. immunization with either adjuvant. We conclude that dmLT and mmCT enhance both induction and persistence of the neonatal immune response to the vaccine Pn1-CRM197, following mucosal or parenteral immunization. This indicates that dmLT and mmCT are promising adjuvants for developing safe and effective early life vaccination strategies.